An Overview of Existing Publications and Most Relevant Projects/Platforms on the Use of Blockchain in Medicine and Neurology - Hort, Jakub; Vališ, Martin; Zhang, Bing; Kuča, Kamil; Angelucci, Francesco (Frontiers in Blockchain, 2021)
Background: Blockchain is a new methodology involving a data structure with list of records, called blocks, which are linked using cryptography. The aim of the review is to overview the existing publication, projects and platforms on the use of blockchain in Medicine and Neurology. Methods: We searched the bibliographic database of MEDLINE. We also accessed ICObench and Coinmarketcap databases to explore upcoming, ongoing, and ended projects. Results: In medicine, there are many projects related to health care, disease prevention and promotion of healthy life style. In neurology, only one project looks interesting: Neuro, an ongoing scientific-technical project uniting scientists, engineers and programmers for development of new architectures and algorithms of neural networks. This system may help the research for new drugs for cancer, Alzheimer's and other diseases. Discussion: Among the problems related to neurodegenerative disorders, there is the lack of information on the patient's clinical history that could allow accurate diagnosis and treatment. The possibility of having a register based on blockchain technology could help doctors in choosing the treatment. In the unique publication present in PubMed, it is described how the use of blockchain technology may help scientists to understand individual evolution in short and long terms. Conclusions: The use of the blockchain in neurology is nearly absent and should be encouraged because it can lead to quantifiable benefits in the treatment of neurodegenerative diseases, especially in clinical trials that can fail because of an incorrect patient recruitment.